Thermal degradation of gelatin enhances its ability to bind aroma compounds: Investigation of underlying mechanisms. (October 2018) - Qi, Jun; Zhang, Wen-wen; Feng, Xian-chao; Yu, Jia-hang; Han, Min-yi; Deng, Shao-lin; Zhou, Guang-hong; Wang, Hu-hu; Xu, Xing-lian
Abstract: The objective of this study was to investigate the ability of thermally degraded gelatin to bind aroma compounds such as nonanal, 2-heptanone, 1-octen-3-ol, hexyl acetate and 2-pentyl furan. Binding ability was strongly affected by changes in thermal-degradation products, the structure and surface hydrophobicity of proteins during heating (1–4 h), through analyzing the results of GC-MS, SDS-PAGE, LC-MS/MS, free amino acid, circular dichroism spectra, Fourier transform infrared (FT-IR) spectroscopy, zeta potential, and surface hydrophobicity. Binding ability of gelatin to aroma compounds increased from 12-14% to 29–35% after heating for 4 h. During the first 1 h of heating, there was no significant increase in surface hydrophobicity due to the effects of degradation and unfolding of protein and protein aggregation, thus the increase in zeta potential and free proline caused by gelatin degradation was likely responsible for the increase in binding ability through electrostatic interactions and hydrogen bonding, respectively. After heating for 2–3 h, unfolding and degradation of gelatin played a leading role in exposure of more hydrophobic amino acids on the protein surface, suggesting an enhancement of binding ability due to hydrophobic interaction. Moreover, effects of zeta potential, exposure of more proline on the interface, and increase in free proline caused by protein degradation could also enhance the affinity of gelatin to flavor compounds. After heating for 4 h, exposure of more hydrophobic amino acids and free proline continued to increase flavor-binding ability, although zeta potential decreased. The results provided insight into improving flavor profile of meat matrix. Graphical abstract: Image 1 Highlights: Thermal degradation of gelatin generated free amino acids and peptides. Unfolding and degradation of gelatin increased its flavor-binding ability. The ability of gelatin to bind aroma compounds was enhanced during heating.